ANALISA PERBAIKAN SUSUT ENERGI 20 kV PADA PENYULANG PRIORITAS JARINGAN DISTRIBUSI TEGANGAN MENENGAH DI PT. PLN (PERSERO) ULP SAMPANG - Sydney, Agnes Amadea Rullynda; Dhofir, Moch.; Utomo, Teguh (Jurnal Mahasiswa TEUB, 2024)
Population growth and economic activity in Sampang Regency have increased the demand for electricity, creating the need for an adequate power distribution system. Data from UID East Java shows that ULP Sampang had losses of 26.82% in August and 26.05% in September, consisting of technical and non-technical losses. To improve the efficiency of the distribution system in ULP Sampang, it is necessary to analyze and plan the addition of capacitor banks. This analysis will use the Newton-Raphson method in ETAP power flow analysis software. Meanwhile, to determine the location of addition of capacitor banks based on loss sensitivity and reactive power comparison. Among the 9 reinforcements connected to the Sampang substation, the Kedungdungreinforcement has the highest voltage drop value reaching 9.59%, based on the data analysis, condition 7 is the most optimal condition to install capacitors with the following capacity: 1.0914 MVAR at Bus-3, 1.0048 MVAR at Bus-4, 0.9436 MVAR at Bus-6, 0.8564 MVAR at Bus-8, 0.3572 MVAR at Bus-29, and 1.0944 MVAR at Bus-2. The addition of capacitors successfully reduced the voltage drop and power dissipation values up to Condition 7. However, in condition 8, there was an increase in active and reactive power because the capacitor banks were installed without using the loss sensitivity method, focusing only on the bus with the largest power loss. Index Terms— Voltage Drop, Active Power Loss, Capacitor Bank, Sensitivity Analysis, Norm, ETAP